Postharvest Quality Maintenance of Longan Fruit by Ultra Violet-C Incorporated with Salicylic Acid Application - Sonthaya Suiubon; Suriyan Supapvanich; Surassawadee Promyou (My University, 2017)
The purpose of this study was to investigate the effects of salicylic acid (SA) dips incorporated with ultra violet-C (UVC) irradiation on postharvest quality of longan fruit cv. 'Dor' during refrigerated storage at 10°C. The longan fruit were dipped in SA solution at the concentration of 0, 1.0, 2.0 and 3.0 mM before irradiated with 6.6 kJ m-2 UVC. Physicochemical quality attributes including peel colour, taste attributes, fruit decay, sensorial qualities and bioactive compounds were monitored. SA dips incorporated with the UVC irradiation maintained the outer peel lightness (L*), total ascorbic acid (TAA) content and crispness score of flesh as well as lowered colour difference (∆E*) value of outer peel and the reduction total antioxidant capacity (TAC) of the flesh during storage. All treatments did not affect the fruit taste attributes including total soluble solids (TSS), total acidity (TA) and TSS/TA ratio. The fruit dipped with 2.0 and 3.0 mM SA incorporated with the UVC irradiation effectively delayed the fruit decay as well as inhibited off-flavour. The fruit dipped with 2.0 mM SA incorporated with UVC irradiation showed the highest acceptability score and also enhanced the activity of antioxidant enzymes such as ascorbic acid peroxidase (APX), superoxide dismutase (SOD) and catalase (CAT).
Keywords: Flesh; APX; Titratable acid; Organoleptic; Postharvest Quality and Shelf Life Management